Factors necessary for effective corporate waqf management for Malaysian public healthcare - Raja Aishah binti Raja Adnan; Mahazan Abdul Mutalib; Muhammad Ridhwan Ab. Aziz (ISRA International Journal of Islamic Finance, 2022)
Purpose - This research paper aims to determine the factors needed to propose a platform where waqf (Islamic endowment) organizations can collaborate with government public hospitals to develop corporate waqf hospitals. Consequently, the elements of governance and sustainability are included in the management of corporate waqf hospitals thereby leading to the corporatization of public hospitals. Design/methodology/approach - This study adopts the qualitative research methodology and undertakes content analysis of data collected from journal articles, magazines and official websites. Data analysis involves open coding with NVivo 12. Findings - General findings from theliterature review have shown that architectural and engineering fundamentals were essential factors in the success of past waqf hospitals of the era between 8th and 14th centuries. In that era, the decentralized waqf-based hospitals employed the mutawalli (the trustee/manager of the waqf assets) to govern the administration of the hospitals. Present corporate waqf hospitals can exploit the elements identified from past waqfbased hospitals and additionally adopt the private-public partnership model in the form of a mudarabah (profitsharing contract) agreement to design a sustainable waqfgovernancemodel forMalaysian public healthcare services. Research limitations/implications - The proposed platform is designed for a corporate waqf model developed in collaboration between Malaysian waqf institutions and public healthcare services. It abides by both the Malaysian fatwa (Islamic rulings) on waqf and the laws of the Malaysian Government. Practical implications -Thereis potential for developing theMalaysian corporate waqf-governance healthcare model which will enable the hospital to provide better quality healthcare to more patients through upgrading the quality of equipment used in hospitals and/or better facilities at equal or lower costs. Consequently, this will not only improve waqf management and distribution but also result in reduction of government expenditure. Social implications - This research promotes the concept of a corporate waqf hospital which will provide innumerable beneficial healthcare services in terms of improved healthcare quality at affordable costs to the general public and at no cost to the poor and the underprivileged. Originality/value - Although waqf has played an important role as a vehicle for Islamic financing in the society for centuries, a model of collaboration or partnership of waqf with public healthcare services has yet to be explored and developed. With proper corporate governance and well-managed sustainability in a corporate waqf model, this newly developed partnership between waqf institutions and public healthcare providers can be a first step in many more interesting collaborative arrangements that can be established between waqf institutions and public services in the future.
Keywords: 330; Decentralization; Healthcare; Islamic social finance; Mudarabah; Public-private partnership; Waqf governance